2016
DOI: 10.1186/s40064-016-1754-z
|View full text |Cite
|
Sign up to set email alerts
|

Safety enhancement in adult body computed tomography scanning: comparison of iodixanol versus iohexol

Abstract: BackgroundThe aim of this study was to compare the safety and intra-individual contrast enhancement of low-osmolar monomeric iohexol and the iso-osmolar dimeric iodixanol in body computed tomography (CT) scanning.MethodsIn this single center, double-blind, prospective study, a total of 2000 consecutive patients undergoing adult body CT scanning were prospectively enrolled, with 1000 patients assigned to iodixanol and 1000 patients assigned to iohexol. In both groups, the contrast medium was injected at the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…However, none of these results reached the predefined cut off for statistical significance. Our results fairly compares with previously published data from RCTs documenting less patients’ discomfort, minor frequency of AEs and equivalent or higher quality image in association with iodixanol compared with low osmolar CM (Gharekhanloo & Torabian, ; Weiland et al, ; Xiao et al, ). Similarly, results from studies of iodine CM intra‐arterial injection tend to favor iodixanol over low osmolar CM agents by safety profile (Manke et al, ; Manninen et al, ; Rosenberg et al, ; Svensson et al, ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, none of these results reached the predefined cut off for statistical significance. Our results fairly compares with previously published data from RCTs documenting less patients’ discomfort, minor frequency of AEs and equivalent or higher quality image in association with iodixanol compared with low osmolar CM (Gharekhanloo & Torabian, ; Weiland et al, ; Xiao et al, ). Similarly, results from studies of iodine CM intra‐arterial injection tend to favor iodixanol over low osmolar CM agents by safety profile (Manke et al, ; Manninen et al, ; Rosenberg et al, ; Svensson et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, results from studies of iso‐osmolar versus low osmolar CM for the intra‐venous (i.v.) route have been fairly consistent in supporting less frequent discomfort, better safety profile, and greater enhancement of the hepatic, aorta, and portal vein (Gharekhanloo & Torabian, ; Weiland, Marti‐Bonmati, Lim, & Becker, ; Xiao et al, ) in patients receiving iso‐osmolar CM. Risk of CIN development defined at the single patient level upon baseline estimation of the glomerular filtration rate (eGFR) have been repeatedly considered in trials of CIN following iodine CM administration in course of CT scan, with inconsistent results (Davenport, Khalatbari, Cohan, et al, ; Davenport, Khalatbari, Dillman, et al, ; Kim et al, ; Kuhn et al, ; Lima et al, ; McDonald, McDonald, Bida, ; McDonald, McDonald, Comin, ; Thomsen & Morcos, ; Utsunomiya et al, ; Weisbord et al, ).…”
Section: Introductionmentioning
confidence: 76%
“…However, no significant differences in the incidence of overall or contrast-related adverse events were observed/reported between the 2 groups. Similar results from a larger sample of patients were obtained by Xiao et al [72], and confirmed the better safety profile of IOCM. These authors reported a nearly threefold increase in the overall frequency of adverse events using iohexol compared to iodixanol (0.9 vs. 2.5%, p < 0.05).…”
Section: Statement 8 Ct Protocols Should Be Personalized According Tosupporting
confidence: 89%
“…Importantly, these results were obtained with an injection dose approximately 50 times lower than that recommended for iohexol, which is 430 mg per kilogram for body imaging applications. 44 In vivo biodistribution and pharmacokinetics of the PEG− TbNRs were also evaluated by MRI. Short-term pharmacokinetics by dynamic T 2 imaging showed that the PEG−TbNRs were rapidly taken up by the liver, reaching a value of 50% of relative enhancement during the first 30 min after the intravenous administration of PEG−TbNRs (10 mg of Tb) (Figure 7a,b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%